Pemikiran Tasawuf Syekh Nawawi Banten dalam Tafsir Marah Labid - Kartubi, Kartubi (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2007)
This article uncovers Syech Nawawi Banten thoughts on Tasauf (mystical order) in his exegesis, Marah Labib, and its relationship with the contemporary thoughts. This library research employs descriptive Â analytical model where his thoughts on Tasauf are analyzed using content analysis by considering the historical approach to interpret the phenontena, events around his life in the past and then correlate them all with the recent condition. It is found that his thoughts are in line wilh his apprehension of the elan of the holy Quran. His Tasauf is ethical-oriented in nature, and if it is actualized in the believers life, this will bring them into pure obedience (iman) towards Allah, their very Creator.